2011
DOI: 10.4028/www.scientific.net/amm.130-134.942
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Mechanisms of Vanadium Micro-Alloyed Reinforcing Steel Bar

Abstract: High strength vanadium micro-alloyed steel with yield strength of 600MPa has been developed based on commercial 20MnSi steel bar. Experimental methods, such as OM, SEM and TEM, were used to study the experimental steels. Compared with 20MnSi, steel 20MnSiV boasts much finer microstructure, and large numbers of nanometer precipitates exist in the specimens of 20MnSiV. Analysis shows that strength of 20MnSiV dramatically increases through grain refinement strengthening and precipitation hardening of nanometer VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to the application requirements of rebar, the mainly focused the current research on precipitation strengthening, anti-fatigue, anti-corrosion, crack generation, production of new rebar, high-temperature performance [2][3][4] and so on. In the field of precipitation strengthening and anti-fatigue research, Li et al [5] found that the grain refinement and precipitation hardening of nanometer VCN particles were the main reasons for the high strength of 20MnSiV steel. The rich, fine and dispersed V (C, N) precipitates were generated in the rebars when the V/N ratio was about 6, which leading to a better anti-fatigue performance and more enhanced mechanical properties [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the application requirements of rebar, the mainly focused the current research on precipitation strengthening, anti-fatigue, anti-corrosion, crack generation, production of new rebar, high-temperature performance [2][3][4] and so on. In the field of precipitation strengthening and anti-fatigue research, Li et al [5] found that the grain refinement and precipitation hardening of nanometer VCN particles were the main reasons for the high strength of 20MnSiV steel. The rich, fine and dispersed V (C, N) precipitates were generated in the rebars when the V/N ratio was about 6, which leading to a better anti-fatigue performance and more enhanced mechanical properties [6,7].…”
Section: Introductionmentioning
confidence: 99%